Frequency of stress hyperglycemia in admitted patients (2 days to 14 years of age) in Qaem Hospital, Hamadan - Z.Razavi (M.D); I.Ramezani (M.D) (مجله دانشگاه علوم پزشکی گرگان, 2003)
Background and Objective: Stress hyperglycemia (Transient rise of blood sugar during acute physiologic stress) has been reported in adults in conditions such as trauma, burns, stroke, myocardial infraction and patients admitted for any cause in intensive care unit. In pediatric age group stress hyperglycemia occurs in febrile illness and sever gastroenteritis. Prevalence and importance of stress hyperglycemia is not fully appreciated by physicians. This study was designed to find the frequency of stress hyperglycemia in children and infants admitted in Qaem Hospital and comparing it with other studies in Iran and other countries. Physicians’ knowledge about these phenomena prevents unnecessary and sometimes dangerous intervention. Patients with stress hyperglycemia due to acute clinical illness may be at risk of developing diabetes in future and their follow up is important matter. Materials and Methods: This descriptive cross-sectional study was conducted from March 2001 to May 201 on 334 patients admitted in Qaem Hospital who needed blood sampling for diagnostic tests. Known cases of diabetes mellitus and patients who received corticosteroids or beta-agonist agent and dextrose containing intravenous fluids were excluded from study. Blood sugar was determined by glucose oxidas method. On serum samples within 30 minute-1 hour after blood sampling. Hyperglycemia was defined in our study as blood sugar more than 150 mg/dl, fever as 37.5°C auxiliary temperature, and dehydration status defined as criteria of WHO. Results: 334 patients from age 2 days to 14 years had inclusion criteria, of these 59.5% were male and 40.4% were female. 26.3% of patients had variable degrees of dehydration. 23.7% of patients had auxiliary temperature?38.5°C to 40°C. blood sugar were in the range of 37 mg/dl-325 mg/dl and there was stress hyperglycemia in 17 patients (5.1%). Stress hyperglycemia was obviously more observed in patients with higher temperatures, more sever dehydration or clinical deterioration. There was no case of diabetes mellitus throughout 1-year follow up. Conclusion: Stress hyperglycemia is a relatively frequent clinical and laboratory finding in patients admitted in pediatrics and neonatal wards. There is no relation between the stress hyperglycemia and final diagnosis of patients, however the more serious the clinical condition, the higher the temperatures or more sever dehydration rises the likelihood of stress hyperglycemia.